Hospitalization expenses of coronary heart disease inpatients in China: evidence from two hospitals in Ningxia Hui autonomous region - Xu, Chuanchuan; Liu, Rugang; Wang, Jian; Nicholas, Stephen (Frontiers in Public Health, 2024)
Aim The increasing morbidity from coronary health disease (CHD) has imposed a significant social and economic burden in China. We analyzed the factors affecting hospitalization expenses of CHD patients. Design From 2012 to 2018, data on 16726 CHD patients were collected from the hospital information system in Ningxia Hui Autonomous Region. Methods A multiple ordered logistic regression model was used to analyze the factors affecting hospitalization expenses. Results The average hospitalization expense was RMB30998.26±29890.03. Hospital materials expenses accounted for roughly 60% of total hospitalization costs. The elderly, patients who were male, in critical health status, with longer hospital stays, unemployed, using antibiotics and undergoing an operation without incision had significantly raised hospital expenses, while those with fewer complications, no operations and self-paying for health care had reduced hospitalization costs (P < 0.05). The length of hospital stay played a partial mediator role (P < 0.05). Public Contribution Controlling the increase of medical materials costs and preventing over-consumption of hospital services by insured patients are recommended.